Digital Legitimacy: A Narrative Analysis of the Utilization of Management Information Systems for CSR Program Transparency in Public Companies - Tjiwidjaja, Halim (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
The increasing demands for transparency and social accountability in the digital era have encouraged public companies to utilize Management Information Systems (MIS) in managing their Corporate Social Responsibility (CSR) programs. This study aims to explore how MIS is used not only as an operational tool but also as a strategic means to build digital legitimacy in the eyes of stakeholders. This study uses a qualitative approach with a systematic literature review to analyze (1) the legitimacy narrative built by management through MIS, (2) the challenges of CSR data integration, and (3) the changing dynamics of communication between companies and stakeholders. The data used are sourced from content analysis of public secondary data from two public companies in the mining sector, PT. Tambang Emas Nusantara and banking, PT. Bank Mandiri. The findings of this study indicate that the companies build narratives of